A bond of blood - Forrest, Bella (Forrest, Bella. Shade of vampire, 2015)
Derek will rip Caleb's heart out the moment he lays eyes on him for what he's done. Rose is convinced that the vampire is innocent. But my daughter has been fooled. Nobody but Caleb could have stolen away our dear friend. I gaze out at the dark waters rushing past us in the submarine, as we speed closer and closer toward our destination.